Customers Loyalty Through Experiential Marketing on The Salon Crisni in Singaraja - Nurkariani, Ni Luh; Kusuma, Gusti Putu Eka (Universitas Pendidikan Ganesha, 2021)
Business development is currently growing rapidly, one of which is a business engaged in services. In running a beauty salon service business, it is very important to make customers loyal or what is called Customer Loyalty. Customer loyalty is customer commitment to a store brand or supplier based on a very positive attitude in long-term purchases, it is easier to develop and succeed if the company can make customers loyal. The purpose of this study was to determine sense, feel, think, act, relate to customer loyalty at Krisni salon. The analysis technique used in this research is validity and reliability test, multiple regression analysis, multiple correlation analysis, classical assumption test, determination test, t-test and hypothesis test with t-test. The results showed that experiential marketing which consists of sense, feel, think, act, relate has a positive and significant effect on customer loyalty at Krisni salon in Singaraja. These results are proven by testing the hypothesis with the t-test which shows that t-count> t-table and the results of model testing with t-test which show that t-count> t-table. This result means that in creating customer loyalty, Krisni salon must pay attention to the strategies used, one of which is experiential marketing.